Thermal Degradation Kinetics of Encapsulated Palm Carotenes Using Different Combination of Wall Materials - Hong, Khoo Mun; Indrawati, Renny; Brotosudarmo, Tatas HP; Limantara, Leenawaty (Indonesian Journal of Natural Pigments, 2020)
Palm oil is known as one of the richest sources of carotenes. Carotenes concentrate could be prepared from crude palm oil and possessing potency to be used as nutraceutical materials. Due to the susceptibility of carotenes against heat, the encapsulation procedure might be applied to provide protections. The present study was aimed to learn the influence of using different combination of wall materials toward the thermal degradation kinetics of palm carotenes. Maltodextrin was used as primary wall material, being combined with various surface-active agents, i.e. Tween-80 (A), Tween-20 (B), and Arabic gum (C). The carotenes concentrate was encapsulated through emulsification steps, and the vivid yellow powder was obtained after freeze drying process. Then, encapsulated palm carotenes were stored in 200C, 350C, and 500C for several days, and the color, carotenes spectrum, as well as water content were monitored periodically. The kinetics of thermal degradation of carotenes were estimated using Arrhenius equation. The results showed that the use of different combination of wall materials exhibited distinct degradation rate. The combination of maltodextrin and Tween-80 gave preferable protection compared to the others, being half-degraded after 51 days in 200C.